Situational predictors of sexual risk episodes among men with HIV who have sex with men. Issue 6 (21st November 2008) - Wilson, P A; Cook, S; McGaskey, J; Rowe, M; Dennis, N
Abstract : Background: Men with HIV who have sex with men (MSM) represent the largest group of people living with HIV/AIDS in the United States. It is important to understand the sexual risk-taking behaviours that may be linked to the transmission of HIV and other sexually transmitted infections in this population. Models of HIV risk that focus solely on personal factors have been demonstrated to be ineffective at explaining risk behaviour. Rather, in order to fully understand sexual risk-taking, it is important to examine the factors linked to high-risk sexual situations and not solely the factors linked to potentially high-risk people. Methods: A diverse sample of 100 MSM with HIV completed a 6-week internet-based sex diary that collected detailed information on recent sexual encounters. In total, information on over 250 sexual episodes was collected and analysed. Generalised linear mixed models were used to examine situational predictors of risk episodes. Results: Analyses revealed that drug use by self and sex partners (examined individually and together) were positively related to risk episodes. Likewise, having a sex partner met online and having a sexual encounter in a sex party or bathhouse setting was linked to risk episodes. Sexual episodes that involved a sex-partner who was perceived as sexually desirable and those involving communication about HIV and/or condom use with partners each were negatively related to risk. Conclusions: Situational factors play an important role in explaining sexual risk-taking among MSM with HIV. Researchers should place a greater focus on drug use and characteristics of sex partners and settings in which sexual behaviours occur as situational predictors of risk in order to comprehensively understand sexual risk-taking in this population.